PERANCANGAN SISTEM INFORMASI PRODUKSI SABLON BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE PADA INFINITEES - Adi Setiawan; Santosa Wijayanto (Lembaga Pengembangan Kinerja Dosen, 2023)
Infinitess store in its production activities has been using computers, but still limited to spreadsheets. As its business grows, the limitations of spreadsheets become increasingly evident. All data collection is still done manually, starting from recording customer orders, inventory data collection of raw materials, scheduling production processes, and monitoring production processes. This research aims to design a web-based screen printing production information system at Infinitees store to improve service and facilitate information availability in the production process. The method used in the design is Prototype method. For the design, HTML and PHP are used, as well as MySQL as the database. The expected result of this research is to build and design a web-based screen printing production information system to facilitate data collection processes and present information related to the production process easily and quickly.